ANALYSIS OF COPING STRATEGY TRENDS IN JUNIOR HIGH SCHOOL STUDENTS - Seni Ratna Ayu; Gian Sugiana Sugara; Muhammad Muhajirin (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2024)
The purpose of this study is to describe the description of coping strategy trends in grade VIII students. This study is a quantitative research with a descriptive method. The population in this study is 221 students in grade VIII. The sampling technique in this study uses simple random sampling. The results of the study show that in general, the tendency of coping strategies of grade VIII students to have coping strategy skills is in the medium category. Students in the low category amounted to 33 people or equivalent to 15%. Students in the medium category amounted to 160 people or equivalent to 72%. The number of students in the high category is 28 people, or equivalent to 13%. The significance of coping strategy ability in male and female students, showed a Sig result of 0.89 0.05 which means that there was no significant difference between coping strategy ability in male and female students in grade VIII.